METAFORA KONSEPTUAL DALAM LUKAS GRAHAM 3 THE PURPLE ALBUM: ANALISIS SEMANTIK KOGNITIF - Afni Apriliyanti Devita; Tajudin Nur (Jurnal Semantik, 2020)
This study is a cognitive semantik analysis regarding the use of metaphors in song lyrics. The method used is the descriptive qualitative. Lukas Graham is a band from Denmark. The data were taken from 10 songs of Lukas Graham’s 3 The Purple Album. The aims of this study are to discuss (1) metaphorical characteristics in Lukas Graham’s 3 The Purple Album, (2) metaphorical types in Lukas Graham’s 3 The Purple Album, and (3) image schemes contained in Lukas Graham’s 3 The Purple Album. The theory used are the conceptual metaphor of Lakoff and Johnson (2003) as the main theory and the image scheme of  Croft & Cruse (2004). The result showed 21 data of conceptual metaphor with 15 ontological metaphors, 2 orientational metaphors, and 4 structural metaphors. The ontological metaphors is the most dominant in Lukas Graham 3 The Purple Album. The image scheme found in the study were 3 scheme containers, 3 scheme unities, 9 scheme existences, 4 scheme identities, and 2 scheme spaces. The data has a pattern of 1) ontological conceptual metaphor has container, existence, and unity image schemes, 2) orientational conceptual metaphor has space image scheme, and 3) structural conceptual metaphor has identity image schemes.